Peningkatan Kompetensi Guru dalam Menyusun Perangkat Pembelajaran Kurikulum 2013 melalui Metode Pendampingan dan Bimbingan Berkelanjutan pada Guru MI Negeri Kota Blitar - Dwiyani, Nanik (Center of Education Journal (CEJou), 2022)
Blitar City State MI teachers have actually attended 2013 curriculum training. However, there are still many teachers who have difficulty in compiling learning tools. The principal has carried out monitoring and the result is that 10% of teachers can arrange learning tools. Several factors that influence this are due to the busyness of teachers, lack of guidance and assistance and not yet optimal socialization related to the preparation of learning tools. The solution to this problem is to assist in the preparation of learning tools. It aims to improve the competence of teachers in making learning tools. The research uses action research with 2 cycles. In each cycle there are 4 stages consisting of planning, action, observation and reflection. Data were taken from the results of observations and tests. The data were then analyzed using a qualitative descriptive approach. The results showed that after mentoring in the preparation of learning tools, thecompetence of teachers in preparing learning tools increased.